Analytical solution of the systems of nonlinear fractional partial differential equations using conformable Laplace transform iterative method - Nisar Gul; Saima Noor; Abdulkafi Mohammed Saeed; Musaad S. Aldhabani; Roman Ullah (AIMS Mathematics)
In this study, we presented the conformable Laplace transform iterative method to find the approximate solution of the systems of nonlinear temporal-fractional differential equations in the sense of the conformable derivative. The advantage of the suggested approach was to compute the solution without discretization and restrictive assumptions. Three distinct examples were provided to show the applicability and efficacy of the proposed approach. To examine the exact and approximate solutions, we utilized the 2D and 3D graphics. Furthermore, the outcomes produced in this study were consistent with the exact solutions; hence, this strategy efficiently and effectively determined exact and approximate solutions to nonlinear temporal-fractional differential equations.